2006
DOI: 10.1158/0008-5472.can-05-3353
|View full text |Cite
|
Sign up to set email alerts
|

The Aurora Kinase Inhibitor VX-680 Induces Endoreduplication and Apoptosis Preferentially in Cells with Compromised p53-Dependent Postmitotic Checkpoint Function

Abstract: VX-680 is a potent inhibitor of Aurora kinases that induces the accumulation of cells with z4N DNA content, followed by cell death. Here, we define the role of p53 and p21Waf1/Cip1 in cell cycle perturbations following exposure to VX-680. Endoreduplication and apoptosis in response to VX-680 are limited in A549 and MCF-7 cells expressing wild-type p53, and markedly enhanced in cells lacking p53, including those engineered to express the HPV16-E6 oncoprotein or short interfering RNA pools targeting p53. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
161
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(183 citation statements)
references
References 34 publications
(47 reference statements)
18
161
1
3
Order By: Relevance
“…We also exclude three additional protein kinases involved in mitosis as targets for this compound. Interestingly, Aurora A-like inhibitory phenotypes have not previously been reported in cells exposed to VX-680, 15,30 but we now demonstrate phenotypes consistent with inhibition of Aurora A in human cells exposed to the drug, including the appearance of monopolar spindles in mitotic cells, and the suppression of phosphorylation events that are attributable to the inhibition of Aurora A activity. Similar Aurora A-like inhibitory phenotypes have recently been reported with chemically distinct inhibitors of the Aurora kinases, including ZM3 18 and MLN8054, 19 and these findings are all in close agreement with the mitotic phenotype seen in two model eukaryotic organisms, where loss of Aurora A induces a centrosome separation defect and a monopolar spindle phenotype.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We also exclude three additional protein kinases involved in mitosis as targets for this compound. Interestingly, Aurora A-like inhibitory phenotypes have not previously been reported in cells exposed to VX-680, 15,30 but we now demonstrate phenotypes consistent with inhibition of Aurora A in human cells exposed to the drug, including the appearance of monopolar spindles in mitotic cells, and the suppression of phosphorylation events that are attributable to the inhibition of Aurora A activity. Similar Aurora A-like inhibitory phenotypes have recently been reported with chemically distinct inhibitors of the Aurora kinases, including ZM3 18 and MLN8054, 19 and these findings are all in close agreement with the mitotic phenotype seen in two model eukaryotic organisms, where loss of Aurora A induces a centrosome separation defect and a monopolar spindle phenotype.…”
Section: Discussionsupporting
confidence: 63%
“…Prolonged treatment of either HeLa or DLD-1 cells with VX-680 for several days led to the accumulation of polyploid cells and loss of viability, as detected by flow cytometry, consistent with published data with this compound. 16,30 To help clarify the effects of VX-680 on mitosis, we analysed living human DLD-1 cells stably expressing Histone H2B-GFP by time-lapse fluorescence microscopy. Supplementary Movies 1 and 2 document the effects of DMSO or VX-680 on these cells.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…The Aurora kinases represent one such class of molecular targets that are essential for progression through mitosis, and small molecule inhibitors of these kinases possess broad antitumor efficacy that has not yet been shown to discriminate on a cancer genetic basis. 7,11 Although it has been demonstrated that cancer cells deficient in p53 show accelerated polyploidization when treated with VX-680, 23 this does not appear to represent genetic susceptibility per se as cells harboring wild-type p53 are also subject to polyploidization-mediated cell death, though perhaps with delayed kinetics. Our data provide genetic evidence to indicate that the Aurora kinase inhibitor, AZD1152, which is currently undergoing clinical evaluation and potentially of another clinical compound, VX-680, may be relatively ineffective in tumor cells that overexpress MDR1 or BCRP.…”
Section: Discussionmentioning
confidence: 99%
“…9 VX-680 inhibits aurora A and B kinases with low nanomolar potency 11 and the cellular effects are consistent with the inhibition of both aurora A and B kinases, that is, monospindle phenotype, disruption of spindle assembly checkpoint (SAC), aberrant chromosomal segregation, endoreduplication and cytokinesis failure. 12,13 Endoreduplication, the re-replication of DNA in the absence of mitotic division, ultimately results in polyploidy and cell death. It is thought that a p53-dependent postmitotic checkpoint prevents polyploidy.…”
mentioning
confidence: 99%
“…It is thought that a p53-dependent postmitotic checkpoint prevents polyploidy. 13 It is however unclear whether wild-type p53 suppresses polyploidy in cells exposed to aurora kinase inhibitors and, importantly, whether normal cells are also susceptible to these drug effects.…”
mentioning
confidence: 99%